Antinomies and contradictions in the use of nanotechnology in agribusiness - Spoto, Giuseppe (Przegląd Prawa Rolnego, 2025)
The development of new nanomaterial technologies and research into nanoparticles has an impact on many areas, including agriculture and food production. Despite growing interest in nanomaterials, a comprehensive and clear regulatory framework on the subject remains lacking. Regarding their application in food preparation, novel food regulations are key; however, there are some contradictions due to different licensing regimes. For example, titanium dioxide is considered hazardous to health when used as a food additive, yet it continues to be used in drug preparation. This contradiction is explained by the fact that controls and regulations for substances used in food and medicines differ. Research in the broad field of nanotechnology and nanoparticles is closely connected with the debate on the relationship between science, technology and law, as it requires constant updates on issues such as sustainability, responsibility and freedom. The author hopes for greater harmonisation in the dialogue between scientists and jurists in this area, following the model offered in the 1970s by the Asilomar Conference, which increased civil society’s interest in research. It is crucial to avoid ideological barriers and the regulatory bans that often accompany new experiments. Such bans are often driven by unfounded collective fears and political motivations rather than scientific evidence, resulting in bans that are both inexplicable and unreasonable and which only hinder scientific progress.